Impact of sulphuric, hydrochloric, nitric, and lactic acids in the preparation of a blend of agro-industrial digestate and wood ash to produce a novel fertiliser. Issue 1 (February 2021) - Moure Abelenda, Alejandro; Semple, Kirk T.; Lag-Brotons, Alfonso Jose; Herbert, Ben M.J.; Aggidis, George; Aiouache, Farid
Abstract: Anaerobic digestate is a waste product of biogas generation which is produced in large amounts and, because of its high water content, it is expensive to store, transport, and spread to land. Additionally, special conditions are required for land application to minimise the losses of nutrients. This material is primarily used as source of organic matter for soil while farmers continue to rely on NPK chemical fertilisers, which are produced using energy intensive processes. This work evaluated the use of low-pollutant biomass bottom ash as an adsorbent to decrease the availability and the losses of carbon and nutrients. A number of acidification conditions were tested to enhance the adsorption and to improve the dewaterability of the organic waste. The final blend was intended to have a more balanced nutrient profile and to offer better performance in terms of crop growth than the digestate alone. The severe acidifications of the digestate and ash using sulphuric, hydrochloric, nitric, and lactic acids increased more than twice the amount of ammonia which remained in the digestate-ash blend. Hydrochloric acid was found to be the best option for preparation of the ash as sorbent, before mixing with the digestate, and to promote dehydration of the blend to enhance solid-liquid separation. This acid did not reduce the number of active sites in the ash, to promote the chemical stabilisation of the digestate; the addition of the acidified ash reduced the pH below that of the digestate thereby reducing the volatilisation of NH3 from the blend. Graphical Abstract: ga1 Highlights: Acidification enhanced the solid-liquid separation of the digestate. H2 SO4 and CH3 CH(OH)COOH reduced the sorption capacity of the ash. Greater losses of N2 O than NH3 before and after land application by HNO3 acidification. HCl offered the best results in terms of dehydration and activation of the ash. Additional processing is required for the ash before mixing with the digestate.